Graphdiyne bearing pillar[5]arene-reduced Au nanoparticles for enhanced catalytic performance towards the reduction of 4-nitrophenol and methylene blue. Issue 66 (25th November 2019) - Tan, Xiaoping; Xu, Jianhua; Huang, Ting; Wang, Sheng; Yuan, Maojie; Zhao, Genfu
Abstract : Application of a novel 2D heterogeneous hybrid nanomaterial based on graphdiyne and pillar[5]arene-reduced Au nanoparticles in catalyzing the reduction of 4-nitrophenol and methylene blue. Abstract : Graphdiyne (GD), a novel two dimensional (2D) carbon material, has earned a lot of attention in recent years. Constructing a novel hybrid nanomaterial based on GD, macrocyclic host and Au nanoparticles is an effective strategy for heterogeneous catalysis applications. While tremendous advancements in the preparation of two dimensional (2D) materials anchoring Au nanoparticles have been made, it is an urgent requirement to explore a green, efficient and facile approach for obtaining small-sized Au nanoparticles. The use of the 2D material graphdiyne (GD) presents more-promising candidates for constructing excellent sites for loading metal nanoparticles. In this study, a novel 2D heterogeneous hybrid nanomaterial (P5A-Au-GD) based on GD and pillar[5]arene (P5A)-reduced Au nanoparticles (P5A-Au) was successfully prepared. In this strategy, the P5A can reduce HAuCl4 with the aid of NaOH in the dispersion of GD. Accordingly, the generated P5A-Au can immediately interact with GD to form the P5A-Au-GD hybrid nanomaterial without any harsh reduced materials or other energies. The Au nanoparticles with average diameter of 2–3 nm are homogeneously dispersed on the surface of GD. The heterogeneous 2D catalyst of P5A-Au-GD shows high catalytic performances in the reduction of 4-nitrophenol and methylene blue by comparing commercial Pd/C catalyst. Meanwhile, the unique 2D heterogeneous hybrid material P5A-Au-GD exhibits durable recyclability and stability during the catalytic reaction. Considering the outstanding merits of the heterogeneous 2D catalyst of P5A-Au-GD as well as the simple and green preparation, this study might not only present enormous opportunities for the stabilized, high-performance and sustainable catalysts but also be applied in other frontier studies of sustainable functionalized nanocomposites and advanced materials.